Metabolome and transcriptome associated analysis of sesquiterpenoid metabolism in Nardostachys jatamansi - Feng, Mingkang; Chen, Chen; Qu-Bie, Junzhang; Qu-Bie, Axiang; Bao, Xiaoming; Cui, Qi; Yan, Xinjia; Li, Ying; Liu, Yuan; Zhang, Shaoshan (Frontiers in Plant Science, 2022)
Nardostachys jatamansi, an extremely endangered valuable plant of the alpine Himalayas, can synthesize specific sesquiterpenoids with multiple effective therapies and is widely exploited for the preparation of drugs, cosmetics and even religious functions (e.g., well-known spikenard). However, how accumulation trend of the sesquiterpenoids in tissues and the molecular mechanisms underlying the production of the active ingredients are not well understood. This research was mainly to reveal the mechanisms of sesquiterpenoids accumulation and biosynthesis through integrating single-molecule real-time (SMRT) and RNA-seq transcriptome sequencing and phytochemical analysis of the roots, rhizomes, leaves, flowers and anthocaulus. A high-quality full-length reference transcriptome with 26,503 unigenes was generated for the first time. For volatile components, a total of sixty-five compounds were successfully identified by gas chromatography‒mass spectrometry, including fifty sesquiterpenoids. Their accumulation levels in five tissues were significantly varied, and most of the sesquiterpenoids were mainly enriched in roots and rhizomes. In addition, five aromatic compounds were only detected in flowers, which may help the plant attract insects for pollination. For nonvolatile ingredients, nardosinone-type sesquiterpenoids (nardosinone, kanshone C, and isonardosinone) were detected almost exclusively in roots and rhizomes. The candidate genes associated with sesquiterpenoid biosynthesis were identified by transcriptome analysis. Consistently, it was found that most biosynthesis genes were abundantly expressed in the roots and rhizomes according to the functional enrichment and expression patterns results. There was a positive correlation between the expression profile of genes related to the biosynthesis and the accumulation level of sesquiterpenoids in tissues. Gene family function analysis identified 28 NjTPSs and 43 NjCYPs that may be involved in the biosynthesis of the corresponding sesquiterpenoids. Furthermore, gene family functional analysis and gene coexpression network analysis revealed 28 NjTPSs and 43 NjCYPs associated with nardosinone-type sesquiterpenoid biosynthesis. Our research results reveal the framework of sesquiterpenoids accumulation and biosynthesis in plant tissues and provide valuable support for further studies to elucidate the molecular mechanisms of sesquiterpenoid regulation and accumulation in N. jatamansi and will also contribute to the comprehensive utilization of this alpine plant.